Pengaruh Mutasi Kerja, Motivasi Kerja dan Promosi Jabatan terhadap Kinerja Karyawan: (Studi Pada Kantor Badan Pemeriksa Keuangan Republik Indonesia Perwakilan Bali Denpasar) - Erna, Ni Kadek; Suputra, Gusti Alit; Risma M Arsha, I Made (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The goal of this study is to understand how job change, employee motivation, and promotion impact employee performance. 100 respondents made up the sample for this study, which was conducted at the BPK RI Bali Provincial Representative in Denpasar City. Validity Test, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, t Test, and F Test are the data analysis techniques that were employed. Based on the study's findings, it is evident that work mutation significantly improves employee performance, Work motivation has a substantial beneficial influence on employee performance, as does promotion, and work mutation has a big positive effect on employee performance. The independent variable had a 61.1% impact on employee performance. Researchers have suggested that the BPK RI Office of Bali Provincial Representatives in Denpasar City should routinely offer training to employees, that work mutations should take into account the skills of employees and the new positions occupied, that promotions should be given in accordance with applicable terms and conditions, and that employees should face strict sanctions if fraud occurs during the promotion implementation process.